The Effect of Utilizing Marine Electric Energy Sources on the Environment and Economy - Dinanti, Prisila; Sri Sundari; Rudy Laksmono; Try Ridho Ramadhan (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Utilization of renewable energy is by utilizing the available natural potential. One of them is the use of the sea as an electrical energy generator. With the increasingly real threat of the climate crisis, a commitment is needed to reduce the amount of emissions entering the environment. Utilization of the potential of marine power plants is still very minimal compared to other clean energy plants. The use of marine power plants is also still in the research stage and there is no commercial use yet. This is due to several obstacles. The main obstacle is that the funds needed to build a marine power plant are quite large and the lack of adequate technology for converting marine power into electricity. In writing this article using qualitative methods. Qualitative methods are research methods that intend to understand the phenomena discussed by the research subjects. By using a Literature Review to obtain data that will be the topic discussed in this writing. From various locations that are considered to provide potential such as Larantuka, Selayar Islands, Bali, Flores Island, Adonara Island, Toyapakeh Waters in Nusa Penida Bali and the Jeneponto Sea, and of course there are still many coastal areas that have potential as generators but have not yet been detected as capable. produces electrical energy that is comparable to other renewable generators and can contribute to meeting the country's primary electricity needs. The energy results obtained do not contribute to carbon emissions or are in the clean energy category and the tariff for the electricity produced is still affordable